On the Selection of a Centralised or Decentralised Location Structure for the Swedish Migration Agency - A Direction of the Decision Regarding the Structure of the Application Units - Hantoft, Linn; Persson, Malin (My University, 2016)
In 2015 the Swedish Migration Agency experienced a challenge in encountering the explosive increase of asylum seekers. Particular exposed was the first step of the asylum flow, the application process, since it is the part where the asylum seekers are registered into the system and their stay becomes legal. In order to improve the application process, the Agency wanted to investigate how they should structure the application units and if it should be centralised or decentralised. The decision regarding the structure needed to be made with the Agency’s objectives and constraints in mind. The objectives for the application process were to minimise cost, have flexibility in capacity and high customer service, while the constraints were that the Agency needed to encounter the fluctuating inflow of asylum seekers and follow the strategies of their business and of being a public organisation. With this in mind, the purpose of this thesis was to investigate if the Agency should have a centralised or decentralised application unit structure to minimise costs, have flexibility in capacity and high customer service under fluctuating inflow of asylum seekers and defined strategies. The purpose was achieved through a literature study, where relevant theories were presented in a theoretical framework and finally concluded in an analysis model. The analysis model mapped the theoretical constraints and objectives effects on corresponding structure of centralisation or decentralisation. The empirical findings were collected by interviewing eight employees at the Agency and by observing the application unit in Kållered, Gothenburg. Furthermore, data was collected through previous empirical findings and the Agency’s internal data system. The findings were verified and validated in a workshop. The analysis of this thesis was performed by looking into the analysis model and mapping corresponding factors for the current situation at the Agency. The factors importance to the Agency were analysed, where factors of moderate or high importance were taken into account. The result shows that the Agency should have a centralised application unit structure. But, the main conclusion highlights that this is only a direction of the decision and in order to take a definite decision regarding the structure some areas need to be further investigated. The areas worth further investigations are correlations between the factors in the analysis model, impact of the structure decision on the whole asylum flow, factor’s weighting of importance and generalizability of the analysis model for other processes or applicants within the Agency. The recommendations for the Agency is presented in an eight-step figure, where areas and questions worth further attention are presented.
Keywords: Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics; Transport